The perceptions and attitudes of nursing staff in state psychiatric hospitals regarding the causes and treatment of substance abuse and effecting factors - Baysan Arabacı, Leyla; Engin, Esra; Yetmiş, Nihal; Şen, Gülşah; Öztürk, Tülay (Journal of Dependence, 2016)
Objective: This study was performed with the aims of determining the perceptions of nursing staff in psychiatric hospitals regarding the causes and treatment of substance addiction as well as their attitudes towards people with substance abuse problems. Method: This study was carried out with 389 nurses working at 5 state psychiatry hospitals in Turkey. In this study, Demographic Questionnaire, the Causes of Drug Abuse Scale (CADAS), Drug Abuse Scale (CUDAS), Attitudes Scale (AS), and a demographic questionnaire were used. Independent sample t-test, variance, correlation, and linear regression analyses were used. Results: In this study, a negative relationship was established between the nurses’ perception of the causes of substance addiction and their attitude towards people with substance abuse problems; a positive relationship was found between the nurses’ perception of the treatment of substance abuse and their attitude towards people with substance abuse problems (p<0.05). Conclusion: Nursing staff working in psychiatric hospitals in Turkey have the perception that a person takes substances in order to “cope with problems” and for reasons pertaining to his/her “social environment” and in order to recover from substance abuse, they should “avoid the substance” and “seek social-professional help”.